Pyoderma gangrenosum and its syndromic forms: evidence for a link with autoinflammation. (23rd August 2016) - Marzano, A.V.; Borghi, A.; Meroni, P.L.; Cugno, M.
Abstract : What's already known about this topic? Pyoderma gangrenosum is a rare neutrophilic dermatosis usually manifesting as painful ulcers with violaceous, raised and undermined borders on the legs. It presents alone or in the context of syndromic forms like PAPA (pyogenic arthritis, pyoderma gangrenosum and acne), PASH (pyoderma gangrenosum, acne and suppurative hidradenitis) and SAPHO (synovitis, acne, pustulosis, hyperostosis, osteitis). What does this study add? Pyoderma gangrenosum and its syndromes have a peculiar immunological profile suggesting autoinflammation. Interleukin (IL)‐1β is crucial in the pathophysiology of autoinflammatory/neutrophilic dermatoses, and its cross‐talk with IL‐17 may contribute to neutrophil recruitment and activation. IL‐1 blockade represents the most selective treatment for pyoderma and its syndromes, but, in the future, IL‐17 antagonists could also be considered. Linked Comment: Schreml. Br J Dermatol 2016;175 :858 . Summary: Pyoderma gangrenosum is a rare inflammatory neutrophilic dermatosis manifesting as painful ulcers with violaceous, undermined borders on the lower extremities. It may occur in the context of classic syndromes like PAPA (pyogenic arthritis, pyoderma gangrenosum and acne) and SAPHO (synovitis, acne, pustulosis, hyperostosis, osteitis), as well as in a recently described entity named PASH (pyoderma gangrenosum, acne and suppurative hidradenitis). Pyoderma gangrenosum has recently been included within the spectrum of autoinflammatory diseases, which are characterized by recurrent episodes of sterile inflammation, without circulating autoantibodies and autoreactive T cells. In PAPA syndrome, different mutations involving the PSTPIP1 gene, via an increased binding affinity to pyrin, induce the assembly of inflammasomes. These are molecular platforms involved in the activation of caspase 1, a protease that cleaves inactive prointerleukin (pro‐IL)‐1β to its active isoform IL‐1β. The overproduction of IL‐1β triggers the release of a number of proinflammatory cytokines and chemokines, which are responsible for the recruitment and activation of neutrophils, leading to neutrophil‐mediated inflammation. In SAPHO syndrome, the activation of the PSTPIP2 inflammasome has been suggested to play a role in inducing the dysfunction of the innate immune system. Patients with PASH have recently been reported to present alterations of genes involved in well‐known autoinflammatory diseases, such as PSTPIP1, MEFV, NOD2 and NLRP3 . Pyoderma gangrenosum and its syndromic forms can be regarded as a single clinicopathological spectrum in the context of autoinflammation.